Hubungan Persepsi Peserta Didik Tentang Pola Asuh Orang Tua, Kebiasaan Belajar dengan Hasil Belajar - Nur Kholifah; Supriyadi Supriyadi; Suwarjo Suwarjo (Universitas Lampung, 2019)
The purpose of this research was to find out the significant and positive correlation between student perception about parenting parents and learning achievement, learning habits and learning achievement, and student perception about parenting parents and learning habits together with learning achievement thematic of fourth grade students SD Muhammadiyah Metro Central. The type of research was ex-postfacto correlation. Population was 230 and sample was 70 students. Data collection techniques used observation, questionnaire and documentation studies. Data analysis technique used was product moment correlation and multiple correlation. The results showed that there was a significant and positive correlation between student perception about parenting parents and learning achievement indicated at